-Matrix Presentation of Quantum Affine Superalgebra for Type (2 + 1|2) - Wu, Xianghua; Lin, Hongda; Zhang, Honglian (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
In our preceding research, we introduced the Drinfeld presentation of the quantum affine superalgebra associated to the orthosymplectic Lie superalgebra (2 + 1|2) for > 0. We provided the isomorphism between its Drinfeld-Jimbo presentation and Drinfeld presentation using braid group actions as a fundamental method. Based on this work, our current study delves into its -matrix presentation, wherein we establish a clear isomorphism between the -matrix presentation and the Drinfeld presentation. In particular, our contribution extends the investigations of Jing, Liu, and Molev concerning quantum affine algebra in type BCD to the realm of supersymmetry.